2021
DOI: 10.3390/ijerph18115715
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Regulation and Academic Performance in the Academic Context: The Mediating Role of Self-Efficacy in Secondary Education Students

Abstract: Background: in the school stage, adolescents experience different emotional and motivational states involved in the learning process that play a fundamental role in their personal and academic development. In this way, the study focuses on analyzing the relationships between emotional regulation, self-efficacy and academic performance, as well as the possible mediating role of self-efficacy in both. Methods: the study included 2204 students, both male (N = 1193; 54.12%) and female (N = 1011; 45.87%) with ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 48 publications
2
21
0
3
Order By: Relevance
“…There are several scales that measure stress, anxiety, or emotional regulation, and that have been used in many cases in the academic context but focused mainly on university-level students. It can be found the Pre-Examination Anxiety and Uncertainty Coping Scale (COPEAU) [ 5 ]; Academic Stress Inventory (IEA), validated in Spain and designed specifically for the evaluation of academic stress in university students [ 9 ]; Questionnaire of emotional regulation for children and adolescents (ERQ-CA), validated in the Spanish population in the school context between 10 and 19 years [ 35 , 36 ]; Depression Anxiety Stress Scale (DASS-21) [ 37 ]; Scale of Cognitive Anxiety against exams (S-CTAS), Spanish version in university students [ 7 , 38 , 39 ]; Inventory of exam anxiety (TAI), validated in Spanish and adapted to university students [ 40 ]; Inventory of anxiety against the exams-state (STAI), version in Spanish with very good validity to measure anxiety before the exams in university students [ 41 , 42 ]; and Westside Test Anxiety Scale [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several scales that measure stress, anxiety, or emotional regulation, and that have been used in many cases in the academic context but focused mainly on university-level students. It can be found the Pre-Examination Anxiety and Uncertainty Coping Scale (COPEAU) [ 5 ]; Academic Stress Inventory (IEA), validated in Spain and designed specifically for the evaluation of academic stress in university students [ 9 ]; Questionnaire of emotional regulation for children and adolescents (ERQ-CA), validated in the Spanish population in the school context between 10 and 19 years [ 35 , 36 ]; Depression Anxiety Stress Scale (DASS-21) [ 37 ]; Scale of Cognitive Anxiety against exams (S-CTAS), Spanish version in university students [ 7 , 38 , 39 ]; Inventory of exam anxiety (TAI), validated in Spanish and adapted to university students [ 40 ]; Inventory of anxiety against the exams-state (STAI), version in Spanish with very good validity to measure anxiety before the exams in university students [ 41 , 42 ]; and Westside Test Anxiety Scale [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous research conducted with samples of students from both the university level and from secondary and primary education, a statistically significant relationship was found between the level of anxiety and emotions with the situation of facing an exam [ 9 , 35 , 47 , 48 , 49 ]. In addition, a review with meta-analysis allows to clarify that between the ages of 11 and 14, students show a greater negative relationship between anxiety about exams and academic performance compared to upper secondary and university courses [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some control variables are also considered. In order to test the mechanism of agricultural water rebound effect, mediator variables are used in the econometrics model [ 47 , 48 ]. Hence, the mediation model is considered, which can be defined as follows: where i denotes province and t denotes year.…”
Section: Methodsmentioning
confidence: 99%
“…On one hand, the online SN camp played a positive role in promoting the development of students; on the other hand, students might not have had confidence in themselves at the beginning, but they exercised their ability through constant group cooperation and ultimately made continuous progress in the process of learning and building. Previous researches have shown that self-efficacy has a positive effect on student performance (Kim, 2010;Supervía & Robres, 2021). Different from previous studies, this study analyzed students' self-efficacy and the scores of Theme Creative Competition (Activity 7) and found that the mean value of students who won prizes in pre-test and post-test was lower than that of students who did not win prizes (4.821 < 4.838), which is worthy of subsequent discussion and analysis.…”
Section: Finding Of Online Sn Stem Education Campsmentioning
confidence: 98%